Advancing Global Citizenship Education Through Global Competence and Critical Literacy: Innovative Practices for Inclusive Childhood Education. (January 2019) - Anderson, Alida
This article presents a critical policy overview of inclusive education and global citizenship education (GCED) and offers two innovative childhood education practices that support inclusion of children with disabilities through dimensions of physical and conceptual access, both noted implementation barriers to inclusive education across the globe. The first section summarizes global human rights and education initiatives that support GCED through access for children with disabilities in education and in societies. This section addresses questions of how inclusion plays a central role to the advancement of GCED, summarizing major global policy advances to inclusion, and highlighting how advancement of inclusive childhood education supports GCED. This article concludes with two innovative childhood education practices, global competence and critical literacy, which offer critical potential to contribute to GCED through conceptual and physical dimensions of access, and ultimately promote inclusive education.